Sexology in Midwifery - Polona Mivsek, Ana (IntechOpen, 2015)
Midwives support women during the reproductive period of their lives. Dimensions of midwifery work include, in addition to the physiological aspect, psychological and spiritual issues. Midwifery activities mean involvement in the most intimate sphere of clients' lives. Women's perceptions of partnership, sexuality, pregnancy and birth are affected by their personal experiences and by the culture they live in. The same factors also influence the midwives' perception of these issues. It is therefore crucial for the midwives to be aware of certain areas of their work that have a sexual inclination and clarify their own eventual prejudices regarding sexuality, since these can affect their provision of holistic, individual and competent care to women and their families. This book deals with different aspects of sexuality that can have an influence on everyday midwifery work. It might also be of interest to different groups of people - midwives in clinical settings, midwifery educators, midwifery students and also other health professionals who manage women during the reproductive period.